A Facile Method to Establish Human Induced Pluripotent Stem Cells From Adult Blood Cells Under Feeder-Free and Xeno-Free Culture Conditions: A Clinically Compliant Approach. (5th March 2015) - Chou, Bin-Kuan; Gu, Haihui; Gao, Yongxing; Dowey, Sarah N.; Wang, Ying; Shi, Jun; Li, Yanxin; Ye, Zhaohui; Cheng, Tao; Cheng, Linzhao
Abstract : A method for highly efficient human induced pluripotent stem (iPS) cell derivation from adult blood under clinically compliant conditions is reported. The revised episomal vectors and the removal of animal-sourced materials resulted in feeder-free and xeno-free iPS cell generation. Pooled cultures were purified by the presence of the TRA-1-60 pluripotency surface antigen to reduce clonal variations and for repaid iPS cell expansion. These new improvements permit to generate clinically compliant iPS cell lines for therapeutic applications. Abstract: Reprogramming human adult blood mononuclear cells (MNCs) cells by transient plasmid expression is becoming increasingly popular as an attractive method for generating induced pluripotent stem (iPS) cells without the genomic alteration caused by genome-inserting vectors. However, its efficiency is relatively low with adult MNCs compared with cord blood MNCs and other fetal cells and is highly variable among different adult individuals. We report highly efficient iPS cell derivation under clinically compliant conditions via three major improvements. First, we revised a combination of three EBNA1/OriP episomal vectors expressing five transgenes, which increased reprogramming efficiency by ≥10–50-fold from our previous vectors. Second, human recombinant vitronectin proteins were used as cell culture substrates, alleviating the need for feeder cells or animal-sourced proteins. Finally, we eliminated the previously critical step of manually picking individual iPS cell clones by pooling newly emerged iPS cell colonies. Pooled cultures were then purified based on the presence of the TRA-1-60 pluripotency surface antigen, resulting in the ability to rapidly expand iPS cells for subsequent applications. These new improvements permit a consistent and reliable method to generate human iPS cells with minimal clonal variations from blood MNCs, including previously difficult samples such as those from patients with paroxysmal nocturnal hemoglobinuria. In addition, this method of efficiently generating iPS cells under feeder-free and xeno-free conditions allows for the establishment of clinically compliant iPS cell lines for future therapeutic applications.